Religiosity Values: Narrative and Cinematic Analysis in Japanese Slice of Life Film Wood Job! - Saraswati, Agni; Fatmawati, Nindya Galuh (Institut Seni Indonesia Yogyakarta, 2025)
Being religious or “menjadi religius” is a stage above the phase of having a religion, namely “religion”. Faith and obedience to religion can be seen in the manners of daily life not only in rituals. It gives an understanding of goodness, equality, humanity, and justice for others, not only in humans but also in nature. Through its narrative and cinematic aspects, the film can provide answers to problems in life, especially regarding religious knowledge and philosophy of life. The purpose of the study is to find out how Wood Job! (2014) film can provide an immersive experience for the audience. The research methodology involves a multidimensional approach of filmology that includes the narrative (dialogue) and cinematic (mise en scene) languages to see depictions and fragments of daily humanistic life full of religious values. The theoretical approach is David Morgan’s theory of three general modes of embodiment consisting of sacred visual constructions, namely ‘the body before the image, body in the image, and body beyond the image’ in the Religious Studies. The film contains 62 scenes which have 11 scenes depicting religious values in everyday life through its dialogue and mise en scene. This film illustrates religious values in accordance with Shinto beliefs. The result shows ‘the body in the image’ from Yuki’s attitude and ‘the body beyond the image’ from the attitude of the people in Kamusari can be seen in 17,7% from the total scenes. Nilai-Nilai Religiositas: Analisis Naratif dan Sinematik dalam Film Jepang Slice of Life Wood Job! Being religious atau “menjadi religius” merupakan tahap di atas fase having religion, yaitu “beragama”. Beriman dan ketaatan pada agama terlihat dari budi pekerti kehidupan sehari-hari tidak hanya sebatas ritual, namun dapat melahirkan pemahaman kebaikan, kesetaraan, kemanusiaan, dan keadilan kepada sesama makhluk tidak hanya pada manusia namun juga pada alam. Film, baik melalui aspek naratif maupun sinematiknya, mampu memberikan jawaban atas permasalahan hidup, khususnya pengetahuan agama dan filosofi hidup. Tujuan penelitian membedah film Jepang, bergenre drama slice of life, berjudul Wood Job! dianggap mampu memberikan pengalaman mendalam bagi penonton. Metodologi penelitian ini melibatkan pendekatan multidimensi yang mencakup bahasa naratif (dialog) dan sinematik (mise en scene) untuk melihat penggambaran dan penggalan kehidupan sehari-hari yang humanis sarat akan nilai religiusitas. Teori yang digunakan adalah teori religi David Morgan mengenai tiga mode umum perwujudan konstruksi visual sakral, yaitu the body before the image, body in the image, dan body beyond the image dalam Religious Studies. Terdapat total 62 scene yang mencakup 11 scene menggambarkan nilai religiositas dalam keseharian melalui dialog dan mise en scene. Film menampilkan nilai religi yang sesuai dengan kepercayaan Shinto. Hasil penelitian menunjukkan dua mode perwujudan konstruksi visual sakral, the body in the image terlihat dari sikap Yuki dan the body beyond the image terlihat dari sikap masyarakat yang memiliki keyakinan sama di Kamusari yang tercermin dalam 17,7% scene dari keseluruhan total scene.